2012
DOI: 10.1136/annrheumdis-2011-200380
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease is significantly higher in non-smoking treatment-naive rheumatoid arthritis patients: results from a case-control study

Abstract: PD is more frequent and severe in non-smoking DMARD-naive RA patients compared with healthy controls. PD in RA is associated with high titres of ACPAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 24 publications
7
69
3
1
Order By: Relevance
“…In light of recent observations of the presence of inflammation-associated citrullination, presence of PAD-2 and PAD-4 in gingival tissues [28], [48] as well as PPAD in serum [49] now provides good evidence for another important extra-articular source for citrullination and anti-citrullinated protein antibody production to occur years in advance of the development of the clinical signs and symptoms of RA. In this regard it is significant that individuals with untreated RA who are non-smokers but presenting with chronic periodontitis have a significantly high level of anti-citrullinated protein antibody titres [50].…”
Section: Discussionmentioning
confidence: 99%
“…In light of recent observations of the presence of inflammation-associated citrullination, presence of PAD-2 and PAD-4 in gingival tissues [28], [48] as well as PPAD in serum [49] now provides good evidence for another important extra-articular source for citrullination and anti-citrullinated protein antibody production to occur years in advance of the development of the clinical signs and symptoms of RA. In this regard it is significant that individuals with untreated RA who are non-smokers but presenting with chronic periodontitis have a significantly high level of anti-citrullinated protein antibody titres [50].…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The human microbiome plays important roles in immune regulation and self-tolerance. 33 Disturbance of the intestinal microbiome has been linked to several autoimmune diseases, including IBD, 34,35 rheumatoid arthritis, [36][37][38][39][40] and at least 1 category of JIA. 14 After antibiotic treatment, commensal microbial populations often recover within ∼3 months, including in young children.…”
Section: Discussionmentioning
confidence: 99%
“…An important confounder that has been variably reported is smoking status. Although smoking is a well recognized shared risk for rheumatoid arthritis and periodontal disease, Potikuri et al [26 ■■ ] recently reported that the associations are present in nonsmoking rheumatoid arthritis patients.…”
Section: Association Studies Between Periodontal Disease and Rheumatomentioning
confidence: 99%
“…A number of studies [26 ■■ ,58,59 ■ ,60 ■ ] have evaluated whether exposure to Pg is seen in rheumatoid arthritis and whether exposure is associated with rheumatoid arthritis autoantibodies. Using an antibody against Pg , Mikuls et al [58] demonstrated that anti Pg presence and titers were higher in rheumatoid arthritis than controls.…”
Section: Clinical Studies Of P Gingivalis In Rheumatoid Arthritismentioning
confidence: 99%